Workplace Mental Health Awareness Training: A Cluster Randomized Controlled Trial. Issue 4 (April 2021) - Tan, Leona; Harvey, Samuel B.; Deady, Mark; Dobson, Mark; Donohoe, Alison; Suk, Curie; Paterson, Helen; Bryant, Richard
Abstract : Objective: To investigate the efficacy of a workplace mental health awareness training program on help-seeking and mental health outcomes. Methods: A cluster randomized controlled trial was conducted comparing those who received standard training ( N = 210) or standard training with a mental health awareness module ( N = 208). Both groups were followed up for 3 years with the primary outcome being likelihood to seek help. Results: Rates of likely help-seeking were slightly higher in the intervention group 6 months after the training, but this was not maintained over time. There was no significant difference between study conditions for mental health outcomes or actual help-seeking among those with probable mental disorder at any time point. Conclusions: Workplace mental health awareness training has a limited short-term impact on likelihood of help-seeking and does not appear to improve mental health outcomes.